Detection of heartbeat and respiration from optical interferometric signal by using wavelet transform - Šprager, Sebastijan; Zazula, Damjan (Computer methods and programs in biomedicine, 2013)
A novel approach for the heartbeat and respiration detection based on optical interferometer and wavelet transform is proposed in this paper. Optical interferometer is a sensitive device that detects physical elongation of optical fibre due to external perturbations. Mechanical activity of cardiac muscle and respiration reflects in interferometric signal when the interferometer is in contact with human body and, thus, enables unobtrusive detection of human vital signs. The efficiency and accuracy of the proposed approach was estimated in two experimental protocols. The first one collected interferometric signals from 20 subjects during rest. In the second experiment, 10 participants cycled an ergometer until reaching their submaximal heart rate, and were measured immediately after that. Heartbeat detection results show high efficiency (99.46±1.11% sensitivity, 99.60±1.05% precision) and accuracy (mean relative error (MRE) of beat-to-beat intervals 3.16±2.32%) for the first experiment, and slightly lower efficiency (96.22±2.96% sensitivity, 95.35±3.03% precision) and accuracy (MRE of 9.56±3.67%) for the second experiment. Considering respiration detection, high efficiency (97.64±7.28% sensitivity, 99.38±2.80% precision) and accuracy (MRE of intervals between respiration events 7.37±7.20%) for the first experiment, and acceptable efficiency (92.05±6.10% sensitivity, 93.45±3.08% precision) and accuracy (MRE of 16.28±6.25%) for the second experiment confirm a practical value of proposed approaches.